Analyzing commons: complex dynamics leading to sustainably governed urban commons - Müller, Agnes Katharina; Köpper, Julia (Frontiers in Sustainable Cities, 2023)
As a concept, urban commons offer new perspectives on collaborative urban design and the participatory management of urban resources. In many cases, citizens create urban commons as bottom-up initiatives, although they often cooperate with local governments or private proprietors, particularly if a long-term perspective is targeted for their project. Urban commons therefore shed light on the tension between bottom-up initiatives and the public and private sector in urban governance. This article aims to better understand how the interrelation between different variables, such as the implementation process, accessibility of the community, ownership structure, etc., can help to constitute sustainable governed commons. To do so we investigate three case studies of commons in different urban settings by means of field research and interviews with activists. Each case study is evaluated in terms of sustainable governance by identifying enhancing or constraining variables, external conditions, and internal challenges. By analyzing the specific strategies for the different commons using the overarching categories of scale, permeability, and organization, we identify variables that, when combined, can lead to a sustainable managed urban commons. Comparing the different examples makes it possible to assess the limits and possibilities of sustainable urban commons governance.